الأخطاء اللغوية فى التعبير الشفوي لدي طلاب لغير الناطقين بها في كاليمنتان الجنوبية - Oensyar, M. Kamil Ramma (Lugawiyyat, 2024)
Speaking skill is a language ability in pronouncing articulation sounds or uttering words to express thoughts, opinions, and feelings to other people as speakers. Language errors are the use of speech forms of various linguistic units which include words, sentences, paragraphs, which deviate from the system of language rules. Many of the students from Darul Hijrah Islamic boarding School experienced language errors in using Arabic as their daily language. The purpose of this research is to find out the form of errors and factors that cause language errors in students' speaking skills. This research is a qualitative research using a descriptive analysis approach. Data collection techniques were carried out using observation, interviews, and documentation. The subjects of this study were old students and language supervisors at Darul Hijrah Islamic boarding School. Based on the results of the study, linguistic errors in daily conversations made by students of  Islamic boarding School are divided into 7 forms of errors, namely errors in adding letters outside of Arabic, using repeated words, question words, the word "فقط", pronouns, everyday expressions, and Arabic vocabulary. The factors that cause language errors are classified into two parts. Internal factors are; lack of vocabulary, not writing vocabulary, lack of awareness of the importance of language, because of local culture and language, interference of foreign languages in Arabic, due to lack of interest in learning Arabic, often using local languages, do not know vocabulary and do not understand Arabic grammar, not serious about learning Arabic, unable to pronounce Arabic letters. External factors are; Errors in the process of distributing vocabulary both orally and in writing and bad associations among students.